2014
DOI: 10.1039/c3an02329j
|View full text |Cite
|
Sign up to set email alerts
|

Measuring masses of large biomolecules and bioparticles using mass spectrometric techniques

Abstract: Large biomolecules and bioparticles play a vital role in biology, chemistry, biomedical science and physics. Mass is a critical parameter for the characterization of large biomolecules and bioparticles. To achieve mass analysis, choosing a suitable ion source is the first step and the instruments for detecting ions, mass analyzers and detectors should also be considered. Abundant mass spectrometric techniques have been proposed to determine the masses of large biomolecules and bioparticles and these techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 135 publications
0
19
0
Order By: Relevance
“…There have been several recent reviews of high‐mass MS, but they have focused primarily on conventional MS, with only some attention paid to single‐molecule MS (Peng, Chou, & Patil, ; Snijder & Heck, ). Chang reviewed single‐molecule MS in 2009 (Chang, ), but much progress has been made since then.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several recent reviews of high‐mass MS, but they have focused primarily on conventional MS, with only some attention paid to single‐molecule MS (Peng, Chou, & Patil, ; Snijder & Heck, ). Chang reviewed single‐molecule MS in 2009 (Chang, ), but much progress has been made since then.…”
Section: Introductionmentioning
confidence: 99%
“…As with the adoption of different ionization sources, the use of different mass analyzers and data acquisition systems can provide deeper structural insights into lipids of biological interest, resulting in an information-rich dataset [22]. For example, in the case of ion mobility spectrometry (IMS), an additional dimension of information is available by using chemical characterization [22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…49 Such polystyrene microspheres cover the mass range of polymeric nanomaterials investigated in our work, have low size dispersion and have been found to be softly and efficiently transferred in the gas phase by ESI. 74,75 The average mass values obtained from mass distribution for the polystyrene microsphere ions measured by CDMS using the internal calibration were plot- In CDMS, the mass m is calculated using:…”
Section: Electrospray Ionization Single-pass Cdmsmentioning
confidence: 99%
“…As a proof of concept, we demonstrated that single trapped ions can be irradiated by the CO 2 laser leading to photofragmentation patterns. Unfortunately, the "Benner trap" is more a storage device than really a MS/MS instrument, and only lim- In parallel, other technologies 75,[88][89][90][91][92][93] have recently been proposed as MS-based tools for nanometrology. For example, nanomechanical resonators with the size of several hundreds of nm have detected and measured the mass of nanoparticles.…”
Section: The Added Value Of Charge Measurementsmentioning
confidence: 99%